"The Church of Online Support": Examining the Use of Blogs Among Family Caregivers of Persons With Dementia. (February 2017) - Anderson, Joel G.; Hundt, Elizabeth; Dean, Morgan; Keim-Malpass, Jessica; Lopez, Ruth Palan
Many individuals, including dementia caregivers, use blogs to share their experiences. These blogs contain rich narratives representing an untapped resource for understanding the psychosocial impact of caring for a person with dementia at the family level. The present study used blogs written by caregivers of persons with dementia to explore how these individuals leveraged this medium as part of the caregiving experience. Blogs written by self-identified informal caregivers of persons with dementia were identified using a systematic search method, and data were analyzed using a qualitative thematic analysis. Four themes emerged from the narratives: social support through communication and engagement, information gathering and seeking, reminiscing and legacy building, and altruism. By understanding the ways in which individuals providing care for persons with dementia use social media as part of the caregiving experience, family nurses can develop interventions and services aimed at improving caregiver burden and quality of life.